On-farm studies on rice-groundnut vis-a-vis rice-rice sequence system under irrigated dry situations of Telangana: On-farm studies on rice-groundnut vis-a-vis rice-rice sequence system under irrigated dry situations of Telangana - MD LATHEEF PASHA; S SRIDEVI; M GOVERDHAN; G KIRAN REDDY; MD ALIBABA; CH PRAGATHI KUMARI (Journal of Oilseeds Research, 2023)
On farm studies on rice-groundnut vis-a-vis farmers’ practice of rice-rice sequence was conducted in ten peasants’ fields of Medak district of Telangana state. Rice-groundnut sequence realized 9.8% higher mean rice grain equivalent yield (13377 kg/ha) than rice-rice (12186 kg/ha). The mean gross and net returns of diversified sequence were Rs 227407 and 100651/ha, while that of traditional practice were Rs 207157 and 76710/ha respectively. On an average a B C ratio of 1.9 was gained in improved cropping sequence as against the 1.5 under farmers’ practice indicating the profitability of diversified cropping systems.